Democracy in international law-making - Abbasi, Salar, author.
1 online resource.
Keywords: "This book provides a critique of current international law-making and draws on a set of principles from Persian philosophers to present an alternative to influence the development of international law-making procedure. The work conceptualizes a substantive notion of democracy in order to regulate international law-making mechanisms under a set of principles developed between the twelfth and seventeenth centuries in Persia. What the author here names 'democratic egalitarian multilateralism' is founded on: the idea of 'egalitarian law' by Suhrawardi, the account of 'substantial motion' by Mulla Sadra, and the ideal of 'intercultural dialectical democracy' developed by Rūmī. Following a discussion of the conceptual flaws of the chartered and customary sources of international law, it is argued that 'democratic egalitarian multilateralism' could be a source for a set of principles to regulate the procedures through which international treaties are made as well as a criterion for customary international law-ascertainment"--